Should home-based ovulation predictor kits be offered as an additional approach for fertility management for women and couples desiring pregnancy? A systematic review and meta-analysis - Yeh, Ping Teresa (BMJ Glob Health, 2019)
INTRODUCTION: To inform the WHO Guideline on self-care interventions, we conducted a systematic review of the impact of ovulation predictor kits (OPKs) on time-to-pregnancy, pregnancy, live birth, stress/anxiety, social harms/adverse events and values/preferences. METHODS: Included studies had to compare women desiring pregnancy who managed their fertility with and without OPKs, measure an outcome of interest and be published in a peer-reviewed journal. We searched for studies on PubMed, CINAHL, LILACS and EMBASE through November 2018. We assessed risk of bias assessed using the Cochrane tool for randomised controlled trials (RCTs) and the Evidence Project tool for observational studies, and conducted meta-analysis using random effects models to generate pooled estimates of relative risk (RR). RESULTS: Four studies (three RCTs and one observational study) including 1487 participants, all in high-income countries, were included. Quality of evidence was low. Two RCTs found no difference in time-to-pregnancy. All studies reported pregnancy rate, with mixed results: one RCT from the 1990s among couples with unexplained or male-factor infertility found no difference in clinical pregnancy rate (RR: 1.09, 95% CI 0.51 to 2.32); two more recent RCTs found higher self-reported pregnancy rates among OPK users (pooled RR: 1.40, 95% CI 1.08 to 1.80). A small observational study found higher rates of pregnancy with lab testing versus OPKs among women using donor insemination services. One RCT found no increase in stress/anxiety after two menstrual cycles using OPKs, besides a decline in positive affect. No studies measured live birth or social harms/adverse events. Six studies presented end-users’ values/preferences, with almost all women reporting feeling satisfied, comfortable and confident using OPKs. CONCLUSION: A small evidence base, from high-income countries and with high risk of bias, suggests that home-based use of OPKs may improve fertility management when attempting to become pregnant with no meaningful increase in stress/anxiety and with high user acceptability. SYSTEMATIC REVIEW REGISTRATION NUMBER: PROSPERO registration number CRD42019119402.